1999
DOI: 10.4269/ajtmh.1999.60.721
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry and acetylcholinesterase activity of the myenteric neurons of the mouse colon in the chronic phase of experimental Trypanosoma cruzi infection.

Abstract: Abstract. The myenteric plexus of the proximal colon, midcolon, and distal colon was studied in mice chronically infected with the Y strain of Trypanosoma cruzi by means of histochemical methods for NADH-diaphorase and acetylcholinesterase (AChE) on whole mount preparations. Ganglia of infected mice displayed an irregular distribution, with neurons severely altered in form and were found side by side with slightly degenerated or morphologically normal ones. Significant reductions of at least 36% in the numbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 21 publications
3
16
0
1
Order By: Relevance
“…At 75 dpi, the decrease was 52.0% IG 100 and 57.0% IG 1000 (p<0.01) compared to control. These data agree with those of other researchers (Maifrino 1996, Maifrino et al 1999 who observed neuronal decrease from 39.0% to 85.7% in the colon of mice infected with 100 and 1,000 forms of blood trypomastigotes of the strain Y, validating our findings for the establishment of a model of denervation of the chronic infection by T. cruzi in mice. Different authors showed that the colon of humans with Chagas disease presents a neuronal decrease from 55.0% to 66.67% (Adad et al 2001, Silveira et al 2007a.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…At 75 dpi, the decrease was 52.0% IG 100 and 57.0% IG 1000 (p<0.01) compared to control. These data agree with those of other researchers (Maifrino 1996, Maifrino et al 1999 who observed neuronal decrease from 39.0% to 85.7% in the colon of mice infected with 100 and 1,000 forms of blood trypomastigotes of the strain Y, validating our findings for the establishment of a model of denervation of the chronic infection by T. cruzi in mice. Different authors showed that the colon of humans with Chagas disease presents a neuronal decrease from 55.0% to 66.67% (Adad et al 2001, Silveira et al 2007a.…”
Section: Discussionsupporting
confidence: 94%
“…A neuronal death index of 59.0% in the IG 100 and 63.4% in the IG 1000 (p<0.05) was verified when compared to the CG. It was possible to notice that such evaluation was not conducted in former studies (Maifrino 1996, Maifrino et al 1999. Statistic differences (p<0.01) were observed within the same experimental group from 18 to 75 days of infection in both IG 100 and IG 1000 .…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations